Symposium on the Idea of a University in the 1990s - O'Hare, Daniel (Statistical and Social Inquiry Society of Ireland, 1990)
I should like to begin by expressing to SSISI the honour conferred on me in asking me to contribute some personal throughts on 'The idea of a University in the 1990s' and especially because this seminar comemorates the 100th anniversary of Cardinal Newman's death. I wish to emphasise this point in order that the listener will not be left with the impression that these views encompass may total view of the university. The topics which I will refer to are: ? The university in and of the community ? Essential characteristics ? The relationship between academic and managerial autonomy ? Research and the research community ? The workforce - a major focus for the university in the 1990fs ? Demand for higher education - some speculations.
The idea of a university in the 1990s
Read before the Society, 29 March, 1990
Keywords: Third level education; University reform; 314.15